Senior high school students’ writing anxiety: A writing process theory - Naufina, Nurin; Putro, Nur Hidayanto Pancoro Setyo (Universitas Islam Sultan Agung, 2025)
This study examines the three dimensions of writing anxiety (cognitive, somatic, and avoidance) across the four stages of the writing process: prewriting, organizing, writing, and polishing. It also seeks to determine how these dimensions vary by school type. A quantitative approach was utilized, employing a survey design with participation from 202 students enrolled in two senior high schools in Sleman Regency, Yogyakarta, during the 2023/2024 academic year. The schools, categorized as high-performing and moderately-performing, each contributed three Class X sections to the research.Data collection was conducted using a questionnaire of writing anxiety scale and the writing process framework proposed. Analytical techniques such as confirmatory factor analysis and MANOVA were applied. The findings revealed two main results: (1) students' writing anxiety was characterized by three distinct dimensions (cognitive, somatic, and avoidance) observed across all stages of the writing process, and (2) significant variations in these dimensions were identified at the prewriting, organizing, writing, and polishing stages, depending on the school category. This research highlights the complex nature of writing anxiety and its variation across different stages of the writing process and school types. Future studies are encouraged to investigate the underlying causes of stage-specific anxiety, focusing on factors such as individual traits, writing proficiency, and prior experiences.